Early english literacy awareness in kindergaten environment that private shool use, thet must be implement in publich shool - Hernández, Anthony (David, Panamá : UDELAS, 2016)
..
TABLE OF CONTENT GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM CHAPTER II: THEORETICAL FRAMEWORK 2.1. Early Literacy Awareness 2.2. Print motivation 2.2.1. Motivation's components 2.2.2. Children´s excitement 2.2.3. Recompense of reading 2.2.4. Guide children to interact with books 2.3. Print awareness 2.4. Vocabulary 2.4.1. Indirect vocabulary 2.4.1.1. Engage in daily language 2.4.1.2. They listen to adults who read to them 2.4.2. Direct vocabulary 2.4.2.1. Specific words instructions 2.4.2.2. Selecting words to teach 2.4.2.3. Repetition vocabulary 2.5. Narrative skills 2.5.1. Storyboards 2.5.2. Preschoolplay 2.6. Letters knowledge 2.6.1. Key instructional stategies-alphabet knowledge (ABC songs and beyond) 2.7. Phonological awareness 2.7.1. Phonological awareness dimensions 2.7.1.1. First dimension 2.7.1.2. Second dimension 2.8. Development of early english literacy among Loma Colorada Public Shool and Cambridge Bilingual Private School 2.9. Advantages of early literacy awareness 2.10. Early literacy activities CHAPTER III: METHODOLOGICAL ASPECT CHAPTER IV: ANALYSIS AND RESULTS CONCLUSIONS BIBLIOGRAPHY ANNEXES
Incluye Table of content
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopias
Keywords: ENGLISH -- TESIS DE LICENCIATURA; JARDINES INFANTILES -- TESIS DE LICENCIATURA; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; KINDERGARTEN